2021
DOI: 10.1108/jarhe-01-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

Active learning strategies to develop research competences in engineering education

Abstract: PurposeThe purpose of this paper is to implement and evaluate active learning strategies to support engineering students in the development of research competences, contributing to the growing need for a closer relationship between research and teaching.Design/methodology/approachThis study was developed using an action research approach. The data were collected through observations, questionnaire and focus group in order to evaluate the active learning strategies used in the context of the study, based on stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…(Druckman and Ebner, 2008). Literature also documents the effectiveness of the active learning methods and adaptive role-play learning schemes for recognizing and empathizing with the stakeholders beyond the technicalities of a given design or engineering problem (Guerra and Shealy, 2018;Rieg et al, 2022). The core concepts of role-playing also correspond to the desired interdisciplinary knowledge, social skills and technical abilities for BIM in terms of coordination, information exchange and teamwork between project stakeholders (Zhang et al, 2019).…”
Section: Context-based Learning For Bimmentioning
confidence: 99%
See 1 more Smart Citation
“…(Druckman and Ebner, 2008). Literature also documents the effectiveness of the active learning methods and adaptive role-play learning schemes for recognizing and empathizing with the stakeholders beyond the technicalities of a given design or engineering problem (Guerra and Shealy, 2018;Rieg et al, 2022). The core concepts of role-playing also correspond to the desired interdisciplinary knowledge, social skills and technical abilities for BIM in terms of coordination, information exchange and teamwork between project stakeholders (Zhang et al, 2019).…”
Section: Context-based Learning For Bimmentioning
confidence: 99%
“…(Druckman and Ebner, 2008). Literature also documents the effectiveness of the active learning methods and adaptive role-play learning schemes for recognizing and empathizing with the stakeholders beyond the technicalities of a given design or engineering problem (Guerra and Shealy, 2018; Rieg et al. , 2022).…”
Section: Course Framework Learning Setting and The Setupmentioning
confidence: 99%
“…Such university students believe that technology is capable of solving any problems, so they outsource their responsibilities, exempting themselves from the attributions that are assigned to them. 18 However, Rieg et al, 19 analyzed the Brazilian context and showed that active learning strategies enhance the development of critical and observation skills, in addition to written communication. The association between theory and practice from projects that actively involve and lead the student, makes such students develop skills required by the market, in addition to clarifying and fixing the content taught in class.…”
Section: Teaching Of Engineering and Technology In Brazil And Worldwidementioning
confidence: 99%
“…The competencies expected to be demonstrated to achieve accreditation are specified in the professional body documentation. These competencies have regularly been used by education providers to develop learning programmes [14], assess existing training in disaster risk reduction for the built environment sector [15], and discuss educational frameworks that support competence development in built environment conservation [16]. Rather than conducting a questionnaire survey or interviews, which has proved challenging for some authors due to low response rates and difficulties in ensuring representative populations [17], reviewing documentation for each role provided by the relevant professional body was adopted.…”
Section: Stage 1-built Environment Professional Accreditation Body Do...mentioning
confidence: 99%